How Singapore investors can profit from unstructured data - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2017)
Data that is collected in the business environment can be structured or unstructured. In general, structured data refers to information which is highly organised and which can easily be stored in rows and columns within database systems. On the other hand, unstructured data does not have a strict data structure, and is also not organised in a pre-defined manner.